2019
DOI: 10.20944/preprints201903.0260.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deflection Angle of Photon from Magnetized Black Hole and Effect of Nonlinear Electrodynamics

Abstract: In this paper, we analyze deflection angle of photon from magnetized black hole within non-linear electrodynamics with parameter β. In doing so, we find the corresponding optical spacetime metric and then we calculate the Gaussian optical curvature. Using the Gauss-Bonnet theorem, we obtain the deflection angle of photon from magnetized black hole in weak field limits and show the effect of nonlinear electrodynamics on weak gravitational lensing. We also analyzed that our results reduces into Maxwell's electro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Stunningly, this method was shown in a suitable way to calculate the deflection angle in spacetimes with topological defects by cosmic strings and global monopoles [38][39][40][41]. This method has been utilized in various papers for different types of spacetimes [42][43][44][45][46][47][48][49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…Stunningly, this method was shown in a suitable way to calculate the deflection angle in spacetimes with topological defects by cosmic strings and global monopoles [38][39][40][41]. This method has been utilized in various papers for different types of spacetimes [42][43][44][45][46][47][48][49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of the plasma term is apparent in every case such that if ω e /ω ∞ → 0 , all of the above expressions boil down to their non-plasmic counterparts. Conclusively, the influence of plasma is distinctly discernible, as shown graphically by [79].…”
Section: Examples: Black Holesmentioning
confidence: 83%
“…Then, Crisnejo and Gallo showed that the plasma medium deflects photons [41]. For more recent works, one can see [42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82].…”
Section: Introductionmentioning
confidence: 99%